A Qualitative Review on Islamic Sustainable Finance - Silma Lafifa Sunarya; Aam Slamet Rusydiana (AL-MUZARA'AH, 2022)
The current paradigm of Islamic economics and finance leads to comprehensive human development by taking into account the objectives of Islamic sharia (maqasid sharia). This study aims to determine the development and mapping of Islamic Sustainable Finance from research published by reputable journals with the theme of Islamic economics and finance. This study uses a qualitative method with data collection in the form of journal publications from various Scopus-indexed journals with the theme of Islamic Sustainable Finance. There are 154 journal publications with the theme of Islamic Sustainable Finance for the period 1994-2022. The data were processed with Microsoft Excel and analyzed using Nvivo 12 Plus software. The results show a fairly fluctuating increase in journal publications with the theme of Islamic Sustainable Finance. Of the 154 published journals indexed by Scopus, the words that appear the most are Islamic, finance, financial, sustainable, development, social, banking, financing, waqf, and economic with the percentage of each word being 3.22%, 1.55%, 1.50 %, 0.95%, 0.84%, 0.78%, 0.68%, 0.54%, 0.49%, and 0.48%. That is, most states that the development of Islamic finance is sustainable, in terms of banks, social financing, waqf, economics, and so on. This research is expected to add to academic studies related to Islamic finance to achieve a sustainable future for Islamic finance.